2017
DOI: 10.1149/2.1201704jes
|View full text |Cite
|
Sign up to set email alerts
|

An Intermediate-Temperature Oxygen Transport Membrane Based on Rare-Earth Doped Bismuth Oxide Dy0.08W0.04Bi0.88O2-δ

Abstract: In this work, a ceramic oxygen pump based on dysprosium and tungsten co-doped bismuth oxide (DWSB) was synthesized and characterized. The DWSB oxygen ion conducting electrolyte with a composition of Dy 0.08 W 0.04 Bi 0.88 O 2-δ displayed the highest oxygen ion conductivity and was chemically compatible with the La 0.8 Sr 0.2 MnO 3-δ (LSM) electrode material. A composite electrode was fabricated with DWSB-LSM in the mass fraction of 50:50 exhibiting the lowest polarization resistance with the DWSB electrolyte. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In majority of IT-EOGs, the samaria-doped ceria Ce 0.8 Sm 0.2 O 2Àd (SDC), ittria-stabilized bismuth oxide Bi 1.46 Y 0.54 O 3 (YSB), erbia-stabilized bismuth oxide Bi 1.6 Er 0.4 O 3 (ESB), dysprosium-and tungsten-stabilized bismuth oxide Dy 0.08 W 0.04-Bi 0.88 O 1.56 (DWSB), and bilayer SDC/ESB ceramic electrolytes are used. [7][8][9][10][11][12][13] However, the ionic conductivity of these ceramic electrolytes is lower than that of the newly developed solid/ molten Bi 2 O 3 -0.2 wt% B 2 O 3 composite electrolyte (Fig. 1b).…”
mentioning
confidence: 83%
“…In majority of IT-EOGs, the samaria-doped ceria Ce 0.8 Sm 0.2 O 2Àd (SDC), ittria-stabilized bismuth oxide Bi 1.46 Y 0.54 O 3 (YSB), erbia-stabilized bismuth oxide Bi 1.6 Er 0.4 O 3 (ESB), dysprosium-and tungsten-stabilized bismuth oxide Dy 0.08 W 0.04-Bi 0.88 O 1.56 (DWSB), and bilayer SDC/ESB ceramic electrolytes are used. [7][8][9][10][11][12][13] However, the ionic conductivity of these ceramic electrolytes is lower than that of the newly developed solid/ molten Bi 2 O 3 -0.2 wt% B 2 O 3 composite electrolyte (Fig. 1b).…”
mentioning
confidence: 83%
“…11)13) Among them, Hong et al recently reported an excellent oxygen pumping system based on the Dy 0.08 W 0.04 Bi 0.88 O 2¹¤ (DWBO) electrolyte, which shows a high oxide ionic conductivity of 0.13 S cm ¹1 at 650°C, with a La 0.6 Sr 0.4 MnO 3¹¤ /DWBO composite electrode, and demonstrated a high oxygen flux of 2.4 mL cm ¹2 min ¹1 under a DC of 1.0 V at 600°C. 13) This result strongly indicates that the high oxide ionic conductivity of the electrolyte plays an important role in design of a low-power consumption oxygen separation system. Hence, the use of a material whose oxide ionic conductivity exceeds that of DWBO can lead to a further reduction in the operation temperature.…”
mentioning
confidence: 93%
“…One of the important applications is producing N 2 for electrified or retrofitted Haber-Bosch ammonia production plant using green hydrogen produced from water electrolysis. Electrochemical oxygen pumping using cells with oxygen ion conductor such as rareearth doped bismuth oxide Dy 0.08 W 0.04 Bi 0.88 O 2-δ and yttria doped zirconia (YSZ) have been reported for producing high pure oxygen from air (1)(2)(3)(4), with excess air supplied from the cathode compartment. Such a concept has been further developed for N 2 production with controlling the cathode feeding air and oxygen extraction rate for pure oxygen production at the anode compartment and N 2 production at the cathode compartment (5).…”
Section: Introductionmentioning
confidence: 99%